The Role of Governance and Regulation in Shaping ESG Disclosure Quality - Merliyana, Reny Dany (Indonesian Scientific Publication, 2024)
This article provides a narrative review of sustainability accounting and ESG disclosure by synthesizing current literature into four main themes: global trends, regulatory challenges, the link between disclosure and corporate performance, and issues of transparency such as greenwashing. The review aims to make the discussion accessible while maintaining academic rigor. The results demonstrate that while ESG reporting in developed economies has been strengthened by regulatory frameworks such as the EU Corporate Sustainability Reporting Directive, developing countries continue to rely on voluntary and inconsistent disclosure practices. Quantitative evidence indicates a positive association between robust ESG disclosure and corporate outcomes such as profitability, market valuation, and stakeholder trust, though these effects vary across sectors and national contexts. However, significant obstacles persist, including fragmented regulatory approaches, data quality limitations, and misleading practices that erode investor confidence. The discussion highlights the influence of systemic factors such as governance structures, cultural norms, and investor activism, and suggests potential solutions through standardization, independent assurance, and participatory oversight. Future research directions are proposed to address gaps in developing countries and evaluate new regulatory frameworks. These findings reinforce the urgency of advancing ESG disclosure as a credible and impactful mechanism for achieving sustainable corporate transformation.